The unranked infrageneric names validly published in Kalanchoe (Crassulaceae subfam. Kalanchooideae) by Alwin Berger in 1930 revisited, with publication of five names at the rank of section and one at the rank of subgenus - Smith, Gideon F. (Phytotaxa, 2024)
Names at the rank of section are here published for five of the nine unranked infrageneric names that were validly published in Kalanchoe by Alwin Berger in 1930. These are: [1] K. sect. Scapigerae; [2] K. sect. Linearifoliae; [3] K. sect. Socotranae; [4] K. sect. Integrifoliae; and [5] K. sect. Pumilae. These five section names have the corresponding unranked infrageneric names of Berger (1930) as basionyms. For two of Berger’s nine validly published unranked names, [6] K. sect. Stellatopilosae and [7] K. sect. Trichanthae, names had already been validly published at the rank of section, in 2020 and 2023, respectively, with these also having been based on the corresponding two unranked infrageneric names of Berger. For a further one, a new name at the rank of section, [8] K. sect. Raveta, was validly published in 2022. For [9] K. [infragen. unranked] Pubescentes the new status of K. subg. Pubescentes is published. The 10th (and final) unranked name, “K. [infragen. unranked] Crenatae”, of Berger (1930) was not validly published because it included the type of the genus Kalanchoe, and did not repeat the genus name unaltered as its epithet.